ENVIRONMENTAL PSYCHOLOGY AND SPACE SYMBOLISM: AFFECTIVE MAPPING OF THE RELATIONSHIP OF WORKERS IN SOCIAL ASSISTANCE POLICY WITH THEIR WORKPLACES - Lima, Andersson de Castro; Pacheco, Fábio Pinheiro; Bomfim, Zulmira Áurea Cruz (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1115, 2021)
This article presents an investigation that aimed to understand the relations of Social Assistance Policy workers in a city in the state of Ceará with their workplaces. The research is based on contributions from transactional Environmental Psychology and Cultural-Historical Psychology . Affectivity was chosen to elucidate physical-structural and symbolic aspects of human-environmental relations. The Affective Map Generator Instrument was used to measure the workers' Esteem for the Place and analyze their affective images. The results show the prevalence of the image of potentiating and depotentiating contrasts related to the availability of resources and interpersonal relationships. Finally, the work demonstrates a contribution to the management of public policies based on the investigation of human-environmental relations.